Decision Support System for Selection of Healthy Toddler using MOORA Method - Ulfah, Auliana; Hasugian, Abdul Halim (Politeknik Ganesha Medan, 2023)
Toddlers are the human stage after infancy, toddlers are one of the most important stages in the quality development of human growth. one way to develop health in toddlers is to carry out routine checks at Public Health Center. Public Health Center has not yet provided a system for selecting healthy toddlers and also requires a system for selecting healthy toddlers. Therefore a decision support system is needed to make decisions related to checking the health of toddlers. decision support system is part of a computer-based information system, which is used to make a decision, in making a decision support system the Multi Objective Optimization by Ratio Analysis (MOORA) method is used. Based on the calculations made regarding the decision to check the health of toddlers, the MOORA method uses weighting criteria and determines the type of criteria, and MOORA does not have sub-criteria weighting provisions using FMADM, FMADM weighting reduces ambiguity because the bigger the value, the better, but if the value is too large then it is not good, such as body weight. It is necessary to provide more sub-criteria so that the accuracy in ranking is better and more accurate with a scale of 0-5. The optimization value for A1 is obtained by adding the cells from A1 0.6765 + 1.0070 + 0.2626 + 0.1195 = 2.0656 and Alternatives A2, A3, A15 have the most optimal weight values ​​with optimization values ​​(2.3282).